Effects of Lee Silverman Voice Treatment-BIG on Motor, Cognition, Mental Health, Occupational Performance, and Occupational Balance in Patients With Schizophrenia: A Single-Subject Experimental Study - Woo-Hyuk Jang; Sang-Min Seo; Si-Hyun Kim (Occupational Therapy International)
Conclusion: In this study, BIG was found to promote improvement in motor and cognitive function in chronic schizophrenia patients, with positive effects on psychiatric symptoms, task performance, and occupational balance satisfaction.